Fiscal Transparency Initiative : Integration of Natural Resource Management Issues. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper integrates into the Fiscal Transparency Code (FTC) a new fourth pillar (Pillar IV) on natural resource revenue management. This completes the pending update to the IMF's FTC, as set out by staff in 2014 (see IMF 2014a).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet